Combination mechanism investigation on the muscle‐like linear actuator using ionic polymer metal composites. Issue 3 (29th May 2015) - Zhao, Gang; Sun, Zhuangzhi; Guo, Huajun; Zheng, Jinxing; Wang, Haojun; Wang, Zhijie
Abstract : This article primarily focuses on the tandem combination method and parallel combination method fabricating Muscle‐like linear actuator based on ionic polymer metal composites. First, according to the proposed combination methods, muscle‐like linear actuator model was further to manufacture by adopting Bi‐film linear actuator described in our previous work. Subsequently, a series of experiments were done to investigate the performance characteristics of muscle‐like linear actuator including of force output capability and motor coordination capability. Also, some evaluation methods were established to analyze the experimental effect. Finally, experiment results revealed the exiting performance differences through comparing with performance characteristics between the two combination methods, and its relevant combination mechanism was proceeded to clarified. POLYM. COMPOS., 38:479–488, 2017. © 2015 Society of Plastics Engineers